A numerical criterion evaluating the robustness of planetary architectures; applications to the υ Andromedæ system. Issue Volume 15:Issue S364(2019) (October 2021) - Locatelli, Ugo; Caracciolo, Chiara; Sansottera, Marco; Volpi, Mara
Abstract: We revisit the problem of the existence of KAM tori in extrasolar planetary systems. Specifically, we consider the υ Andromedæ system, by modelling it with a three-body problem. This preliminary study allows us to introduce a natural way to evaluate the robustness of the planetary orbits, which can be very easily implemented in numerical explorations. We apply our criterion to the problem of the choice of a suitable orbital configuration which exhibits strong stability properties and is compatible with the observational data that are available for the υ Andromedæ system itself.